Second annual report of the Hospital for Natural Healing : 1936-7 - Hospital for Natural Healing (London, England) (1937)
1937 1937 1930s 13 pages two men known for their wide experience and their true and sincere public spiritedness have almost from the beginning wholeheartedly supported us and taken our Cause right into The House. We are indeed proud and grateful to be associated with our Vice-Presidents and to have retained their interest and support. We hope they will both be with us a very long time and see many of our ambitions materialise. The bulk of our support, financial and otherwise, comes from our patients and their friends, and what could be more convincing proof of our having justified our existence. They are too many in number to thank personally, and their methods of helping are too various to enumerate, but they are not forgotten and their work lives and grows with the life of this institution. CORONATION BAZAAR. For six months Mrs. Washington with the Social Committee and patients and friends behind her, worked for the Coronation Bazaar which was held on June 6th. Mrs. Lyell very kindly came down and opened the Bazaar for us and helped to make it the success it was. In spite of the bus strike preventing many people getting there we were well supported and the decorations and stock were a very convincing proof that those we had helped were willing and anxious to help us in return. HAVE WE PROGRESSED? Early this year a second Treatment Room was opened for Chiropractic, Osteopathic and certain forms of Light Treatment. The staff of Practioners has been increased by two. We are working overtime and could do with a larger staff and larger premises. We hope to have both these improvements in the near future, meanwhile we are very grateful for any help we can get, and if those who think they might be of assistance will come along and say how they think they can help us we shall be only too glad to accept their offer if we can. FUTURE DEVELOPMENTS. It is almost impossible to visualise the future, so much depends on forces outside ourselves. Some of these are very powerful forces and are indirectly responsible for the health and happiness of the people of this Country. There is far too much petty mindedness and fear allowed to influence the work of Public Health — for instance — 7 292/842/2/237